Asymmetric flat ultrafiltration membrane and preparation method thereof
By introducing the removal layer of heavy metals and micro-pollutants composed of β-cyclic paste and amine substances at the bottom layer of the ultrafiltration membrane, the existing ultra-filter membrane cannot remove heavy metals and micro-pollutants in the existing ultra-filter membrane. A more efficient pollutants remove and longer membrane life.
Patent Information
- Application Number
- CN202310888798.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing ultrafiltration membrane cannot effectively remove heavy metal ions and micro-contaminants in water, causing these pollutants to accumulate in human organs and cause harm.
A heavy metal and micropollutant removal layer is introduced at the bottom of the ultrafiltration separation layer of the flat ultrafiltration membrane. It is composed of β-cyclodextrin and amine substances. It is chemically bonded to form a more stable structure, which can adsorb and remove heavy metals and micropollutants. things.
It achieves effective removal of heavy metals and micro-pollutants, extends the life of the ultrafiltration membrane, and does not affect the separation effect and flow rate of the membrane after adsorption.
Abstract
Description
Technical Field
[0001] The invention relates to an asymmetric flat ultrafiltration membrane and a preparation method thereof. Background Art
[0002] In recent years, the concept of healthy water has emerged. For low hardness areas, ultrafiltration water purifiers can be used to retain minerals in the water. my country's tap water contains ppb-level heavy metal ions and micropollutants. However, the separation pore size of the ultrafiltration membrane, the filtering body in the ultrafiltration water purifier, is 2nm-100nm, which is much larger than the size of heavy metal ions and micropollutants. Therefore, the ultrafiltration membrane cannot remove heavy metal ions and micropollutants in the water body only by using the size screening mechanism. Long-term drinking of water containing heavy metal ions and micropollutants will cause heavy metals and micropollutants to accumulate in human organs, which is extremely harmful to the human body. At present, membrane methods, ion exchange, electrodialysis and activated carbon separation are generally used to remove heavy metal ions and micropollutants.
[0003] In recent years, in the field of drinking water, the most common method for removing heavy metals and micropollutants is to use activated carbon, reverse osmosis membrane or nanofiltration. Activated carbon mainly uses its own micropores to adsorb harmful substances, but its adsorption is broad-spectrum and adsorbs a wide variety of substances, such as residual chlorine, humic acid, COD and other substances. Therefore, it is easy to reach adsorption saturation and the removal effect is poor. While reverse osmosis removes heavy metals and micropollutants, it also removes mineral elements that are beneficial to the human body. Nanofiltration membranes have a certain effect on removing heavy metals and micropollutants, but they cannot completely remove heavy metals from water. Other methods for removing heavy metals and micropollutants include ion exchange, electrodialysis, etc. They have problems such as poor removal effect and high cost.
[0004] Traditional ultrafiltration membranes have the advantages of low operating costs, the ability to retain minerals in water, and the ability to effectively treat pollutants such as viruses, high molecular weight organic matter, and colloids. They have been widely used in actual projects. However, ultrafiltration membranes cannot remove heavy metal ions and micropollutants in water bodies by only using a size screening mechanism, and the removal of these pollutants is particularly important in the process of deep wastewater treatment. In order to solve this problem, new ultrafiltration membrane technology is urgently needed to be developed. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an asymmetric flat ultrafiltration membrane and a preparation method thereof, wherein a heavy metal and micro-pollutant removal layer is introduced into the bottom layer of the ultrafiltration separation layer of the flat ultrafiltration membrane, which is more stable and has a longer service life. After the adsorption of heavy metals and micro-pollutants, the separation effect and flow rate of the ultrafiltration membrane itself are not affected; the heavy metal and micro-pollutant removal layer is composed of β-cyclodextrin and amine substances, and the functions of the two in removing heavy metals and micro-pollutants complement each other.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] One of the technical solutions provided by the present invention is: an asymmetric flat ultrafiltration membrane, characterized in that the asymmetric flat ultrafiltration membrane comprises an ultrafiltration separation layer and a heavy metal and micro-pollutant removal layer, the ultrafiltration separation layer is composed of a surface layer and a bottom layer, one outer surface of the bottom layer is in close contact with the surface layer, and the other outer surface is connected to the heavy metal and micro-pollutant removal layer, and the bottom layer and the heavy metal and micro-pollutant removal layer are bonded by chemical bonds. The asymmetric flat ultrafiltration membrane meets one or more of the following conditions:
[0008] a. The heavy metal and micro-pollutant removal layer and the ultrafiltration separation layer are connected via an amide bond; the heavy metal and micro-pollutant removal layer preferably comprises an amino group, and the bottom layer in the ultrafiltration separation layer preferably comprises a carboxyl group;
[0009] b. The thickness of the heavy metal and micro-pollutant removal layer is 50 to 1000 nm, for example, 100 nm, 300 nm or 600 nm;
[0010] c. The thickness of the ultrafiltration separation layer is 200-250 μm, for example, 100 μm, 150 μm or 200 μm;
[0011] d. The thickness of the surface layer in the ultrafiltration separation layer is 0.1-1.5 μm, for example, 1 μm;
[0012] e. The thickness of the bottom layer in the ultrafiltration separation layer is 50-250 μm, for example, 99 μm, 149.5 μm or 198.5 μm.
[0013] The asymmetric flat ultrafiltration membrane of the present invention is a conventional ultrafiltration membrane in the art, and the membrane pore size is 1 to 100 nm.
[0014] The second technical solution provided by the present invention is: a method for preparing an asymmetric flat ultrafiltration membrane, which comprises the following steps: firstly grafting one of the active groups of the bottom layer of the ultrafiltration separation layer for realizing chemical bond bonding, and then reacting with the heavy metal and micro-pollutant removal layer; the ultrafiltration separation layer is composed of a surface layer and a bottom layer, and an outer surface of the bottom layer is in close contact with the surface layer.
[0015] The grafting adopts the irradiation grafting method. Preferably, the irradiation grafting method is to place the bottom layer of the ultrafiltration separation layer upward and perform irradiation grafting under ultraviolet light;
[0016] Furthermore, the radiation grafting satisfies one or more of the following conditions:
[0017] a. The power of the ultraviolet lamp is 20-200W, for example 50w, 100w or 180w;
[0018] b. The dominant wavelength of the ultraviolet lamp is 290-400nm, for example, 300nm, 350nm or 380nm;
[0019] c. The distance between the ultraviolet lamp and the ultrafiltration separation layer is 5 to 20 cm, for example 8 cm, 10 cm or 18 cm;
[0020] d. The radiation grafting time is 5 to 30 minutes, for example, 15 minutes, 20 minutes or 25 minutes.
[0021] The active groups are provided by vinyl carboxylic acid substances;
[0022] And / or, the reaction comprises the following steps: the grafted ultrafiltration separation layer is reacted with a β-cyclodextrin aqueous solution and an amine substance aqueous solution in sequence.
[0023] The operation of reacting with the β-cyclodextrin aqueous solution satisfies one or more of the following conditions:
[0024] a. The concentration of β-cyclodextrin in the aqueous solution is 1 to 10 wt%, for example, 2 wt%, 4 wt% or 8 wt%;
[0025] b. The reaction temperature is 50-80°C, for example 60°C, 70°C or 80°C;
[0026] c. The reaction time is 5 to 12 hours, for example 6 hours or 10 hours.
[0027] The operation of reacting with the aqueous solution of amine substances satisfies one or more of the following conditions:
[0028] a. The amine substance is one or more of chitosan, polyethyleneimine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, preferably polyethyleneimine and / or chitosan;
[0029] b. The concentration of the amine substance in the aqueous solution is 1 to 10 wt%, for example, 2 wt%, 5 wt% or 9 wt%;
[0030] c. The reaction temperature is 60 to 90°C, for example 70°C or 90°C;
[0031] d. The reaction time is 10 to 24 hours, for example 15 hours, 20 hours or 24 hours.
[0032] The method for preparing an asymmetric flat ultrafiltration membrane satisfies one or more of the following conditions:
[0033] a. The ultrafiltration separation layer is a polysulfone ultrafiltration membrane;
[0034] b. The vinyl carboxylic acid substance is one or more of acrylic acid, butenoic acid and pentenoic acid, preferably 2-butenoic acid or acrylic acid;
[0035] c. The concentration of the solution of the vinyl carboxylic acid substance is 2wt%-20wt%, for example, 5wt%, 8wt% or 15wt%.
[0036] In the present invention, the method for preparing an asymmetric flat ultrafiltration membrane further comprises washing the ultrafiltration membrane after the reaction and storing it in a 1wt% to 3wt% sodium bisulfite solution, preferably a 3wt% solution, for standby use.
[0037] The third technical solution provided by the present invention is: an asymmetric flat ultrafiltration membrane. The asymmetric flat ultrafiltration membrane is prepared by the preparation method as described above.
[0038] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0039] The reagents and raw materials used in the present invention are commercially available.
[0040] The positive and progressive effects of the present invention are:
[0041] (1) The heavy metal and micro-pollutant removal layer exists in the bottom layer of the ultrafiltration membrane in a grafted manner, which is more stable and has a longer service life. Compared with the heavy metal and micro-pollutant removal layer existing on the surface and in the membrane pores of the ultrafiltration membrane, the adsorption of heavy metals and micro-pollutants does not affect the separation effect and flow rate of the membrane itself. After the adsorption of heavy metals and micro-pollutants, the flow rate of the membrane remains basically unchanged.
[0042] (2) The main function of β-cyclodextrin is to adsorb micropollutants. In addition, its cavity can also chelate heavy metals and has a certain heavy metal adsorption capacity. The main function of amine substances is to adsorb heavy metals. Since amino groups are easily protonated, they also have a certain removal capacity for micropollutants at negative charge points. The two complement each other, giving the membrane super strong heavy metal and micropollutant removal performance. When the concentration of heavy metal adsorption of Cd(NO3)2 is less than 5ppb, the maximum amount of water in the membrane that passes through the spiked solution can reach 5.7L. When the concentration of micropollutant adsorption of bisphenol A is less than 10ppb, the maximum amount of water in the membrane that passes through the spiked solution can reach 6.2L. DETAILED DESCRIPTION
[0043] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0044] Example 1
[0045] (1) applying a 5 wt % 2-butenoic acid solution to the bottom layer of the polysulfone ultrafiltration separation layer, wherein the thickness of the polysulfone ultrafiltration separation layer is 100 μm, and the thickness of the bottom layer of the polysulfone ultrafiltration separation layer is 99 μm;
[0046] (2) Place the bottom layer of the polysulfone ultrafiltration separation layer on a table with the bottom layer facing upward, directly below the ultraviolet lamp. Turn on the 100W ultraviolet lamp for 20 minutes; the main wavelength of the ultraviolet lamp is 300nm, and the distance between the ultraviolet lamp and the ultrafiltration separation layer is 8cm.
[0047] (3) washing the ultrafiltration separation layer and placing it in a 2 wt % β-cyclodextrin (β-CD) aqueous solution at 80° C. for 6 h;
[0048] (4) After washing the ultrafiltration membrane, place it in a 2% polyethyleneimine aqueous solution and react at 70° C. for 20 h. The thickness of the heavy metal and micropollutant removal layer obtained is 100 nm.
[0049] (5) After the reaction is completed, the polysulfone ultrafiltration membrane is cleaned and stored in a 3 wt % sodium bisulfite (NaHSO 3 ) solution for later use.
[0050] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in the test fixture and pre-pressed at a pressure of 0.2 MPa for 30 min. At 0.1 MPa, the flow rate was measured to be 230 LMH;
[0051] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. A 25 ppb cadmium nitrate (Cd(NO3)2) solution was used as the spiked solution. When the Cd(NO3)2 concentration in the solution passing through the membrane was greater than 5 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 3.9 L. After the heavy metal adsorption test was completed, the flow rate was measured to be 227 LMH at 0.1 MPa, and the flow rate did not change much.
[0052] (7) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test tooling and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spiked solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 4.3 L. After the micropollutant adsorption test was completed, the flow rate was measured to be 223 LMH at 0.1 MPa, and the flow rate did not change much.
[0053] Example 2
[0054] (1) applying a 15 wt % acrylic acid solution to the bottom layer of the polysulfone ultrafiltration separation layer, wherein the thickness of the polysulfone ultrafiltration separation layer is 150 μm, and the thickness of the bottom layer of the polysulfone ultrafiltration separation layer is 149.5 μm;
[0055] (2) Place the bottom layer of the polysulfone ultrafiltration separation layer upward on a table, directly below the ultraviolet lamp. Turn on the 180W ultraviolet lamp for 25 minutes; the main wavelength of the ultraviolet lamp is 350nm, and the distance between the ultraviolet lamp and the ultrafiltration separation layer is 10cm.
[0056] (3) washing the ultrafiltration separation layer and placing it in an 8 wt % β-cyclodextrin (β-CD) aqueous solution at 70° C. for 10 h;
[0057] (4) After washing the ultrafiltration membrane, the membrane was placed in a 9 wt % aqueous solution of polyethyleneimine and reacted at 90° C. for 15 h. The thickness of the heavy metal and micropollutant removal layer obtained was 600 nm.
[0058] (5) After the reaction is completed, the polysulfone ultrafiltration membrane is cleaned and stored in a 3 wt % sodium bisulfite (NaHSO 3 ) solution for later use.
[0059] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in the test fixture and pre-pressed at a pressure of 0.2 MPa for 30 min. At 0.1 MPa, the flow rate was measured to be 154 LMH;
[0060] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. A 25 ppb cadmium nitrate (Cd(NO3)2) solution was used as the spiked solution. When the Cd(NO3)2 concentration in the solution passing through the membrane was greater than 5 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 5.7 L. After the heavy metal adsorption test was completed, the flow rate was measured to be 154 LMH at 0.1 MPa, and the flow rate did not change.
[0061] (7) A flat nanofiltration membrane with a diameter of 53 mm was placed in a test fixture and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spiked solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 6.2 L. After the micropollutant adsorption test was completed, the flow rate was measured to be 150 LMH at 0.1 MPa, and the flow rate did not change much.
[0062] Example 3
[0063] (1) applying 8% acrylic acid solution to the bottom layer of the polysulfone ultrafiltration separation layer by scraping, wherein the thickness of the polysulfone ultrafiltration separation layer is 200 μm, and the thickness of the bottom layer of the polysulfone ultrafiltration separation layer is 198.5 μm;
[0064] (2) Place the bottom layer of the polysulfone ultrafiltration separation layer upward on a table, directly below the ultraviolet lamp. Turn on the 50W ultraviolet lamp for 15 minutes; the main wavelength of the ultraviolet lamp is 380nm, and the distance between the ultraviolet lamp and the ultrafiltration separation layer is 18cm.
[0065] (3) After washing the ultrafiltration membrane, place it in a 4 wt % β-cyclodextrin (β-CD) aqueous solution and react at 60° C. for 10 h;
[0066] (4) After washing the ultrafiltration membrane, place it in a 5 wt % aqueous solution of polyethyleneimine and react at 70° C. for 24 h. The thickness of the heavy metal and micropollutant removal layer obtained is 300 nm.
[0067] (5) After the reaction is completed, the polysulfone ultrafiltration membrane is cleaned and stored in a 3 wt % sodium bisulfite (NaHSO 3 ) solution for later use.
[0068] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in the test fixture and pre-pressed at a pressure of 0.2 MPa for 30 min. At 0.1 MPa, the flow rate was measured to be 279 LMH;
[0069] (6) Take a flat ultrafiltration membrane with a diameter of 53 mm and put it into the test tooling to test its heavy metal adsorption performance. Use a 25 ppb cadmium nitrate (Cd(NO3)2) solution as the spiked solution. When the Cd(NO3)2 concentration in the solution passing through the membrane is greater than 5 ppb, the test is stopped. The final amount of water passing through the membrane with the spiked solution is 3.5 L. After the heavy metal adsorption test is completed, the flow rate is measured at 0.1 MPa to be 280 LMH, with little change in the flow rate.
[0070] (7) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test tooling and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spiked solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 3.7 L. After the micropollutant adsorption test was completed, the flow rate was measured to be 275 LMH at 0.1 MPa, and the flow rate did not change much.
[0071] Comparative Example 1
[0072] (1) applying a 5 wt % 2-butenoic acid solution to the surface of a polysulfone ultrafiltration separation layer, wherein the thickness of the polysulfone ultrafiltration separation layer is 100 μm, and the thickness of the surface of the polysulfone ultrafiltration separation layer is 1 μm;
[0073] (2) Place the polysulfone ultrafiltration separation layer with the surface facing upward on a table, directly below the ultraviolet lamp. Turn on the 100W ultraviolet lamp for 20 minutes; the main wavelength of the ultraviolet lamp is 300nm, and the distance between the ultraviolet lamp and the ultrafiltration separation layer is 8cm.
[0074] (3) After washing the ultrafiltration membrane, place it in a 2 wt % β-cyclodextrin (β-CD) aqueous solution and react at 80° C. for 6 h;
[0075] (4) After washing the ultrafiltration membrane, place it in a 2% polyethyleneimine aqueous solution and react at 70° C. for 20 h. The thickness of the heavy metal and micropollutant removal layer obtained is 100 nm.
[0076] (5) After the reaction is completed, the polysulfone ultrafiltration membrane is cleaned and stored in a 3 wt % sodium bisulfite (NaHSO 3 ) solution for later use.
[0077] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in the test fixture and pre-pressed at a pressure of 0.2 MPa for 30 min. At 0.1 MPa, the flow rate was measured to be 230 LMH;
[0078] (6) A flat ultrafiltration membrane with a diameter of 53 mm was placed in a test fixture and its heavy metal adsorption performance was tested. A 25 ppb cadmium nitrate (Cd(NO3)2) solution was used as the spiked solution. When the Cd(NO3)2 concentration in the solution passing through the membrane was greater than 5 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 3.9 L. After the heavy metal adsorption test was completed, the flow rate was measured at 0.1 MPa to be 201 LMH, and the flow rate decreased significantly.
[0079] (7) A flat nanofiltration membrane with a diameter of 53 mm was placed in the test tooling and its micropollutant adsorption performance was tested. A 50 ppb bisphenol A (BPA) solution was used as the spiked solution. When the BPA concentration in the solution passing through the membrane was greater than 10 ppb, the test was stopped. The final amount of water passing through the membrane with the spiked solution was 4.3 L. After the micropollutant adsorption test was completed, the flow rate was measured to be 194 LMH at 0.1 MPa, and the flow rate decreased significantly.
Claims
1. An asymmetric flat ultrafiltration membrane, characterized in that: The asymmetric flat ultrafiltration membrane comprises an ultrafiltration separation layer and a heavy metal and micro-pollutant removal layer, wherein the ultrafiltration separation layer is composed of a surface layer and a bottom layer, wherein one outer surface of the bottom layer is in close contact with the surface layer, and the other outer surface is connected to the heavy metal and micro-pollutant removal layer, and the bottom layer is bonded to the heavy metal and micro-pollutant removal layer through a chemical bond.
2. The asymmetric flat ultrafiltration membrane according to claim 1, characterized in that: The asymmetric flat ultrafiltration membrane meets one or more of the following conditions: a. The heavy metal and micro-pollutant removal layer and the ultrafiltration separation layer are connected via an amide bond; the heavy metal and micro-pollutant removal layer preferably comprises an amino group, and the bottom layer in the ultrafiltration separation layer preferably comprises a carboxyl group; b. The thickness of the heavy metal and micro-pollutant removal layer is 50 to 1000 nm, for example, 100 nm, 300 nm or 600 nm; c. The thickness of the ultrafiltration separation layer is 200-250 μm, for example, 100 μm, 150 μm or 200 μm; d. The thickness of the surface layer in the ultrafiltration separation layer is 0.1-1.5 μm, for example, 1 μm; e. The thickness of the bottom layer in the ultrafiltration separation layer is 50-250 μm, for example, 99 μm, 149.5 μm or 198.5 μm.
3. A method for preparing an asymmetric flat ultrafiltration membrane, characterized in that: The method comprises the following steps: firstly grafting one of the active groups of the bottom layer of the ultrafiltration separation layer for realizing chemical bond bonding, and then reacting with the heavy metal and micro-pollutant removal layer; the ultrafiltration separation layer is composed of a surface layer and a bottom layer, and an outer surface of the bottom layer is in close contact with the surface layer.
4. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 3, characterized in that: The grafting adopts the irradiation grafting method. Preferably, the irradiation grafting method is to place the bottom layer of the ultrafiltration separation layer upward and perform irradiation grafting under ultraviolet light; Furthermore, the radiation grafting satisfies one or more of the following conditions: a. The power of the ultraviolet lamp is 20-200W, for example 50w, 100w or 180w; b. The dominant wavelength of the ultraviolet lamp is 290-400nm, for example, 300nm, 350nm or 380nm; c. The distance between the ultraviolet lamp and the ultrafiltration separation layer is 5 to 20 cm, for example 8 cm, 10 cm or 18 cm; d. The radiation grafting time is 5 to 30 minutes, for example, 15 minutes, 20 minutes or 25 minutes.
5. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 3, characterized in that: The active groups are provided by vinyl carboxylic acid substances; And / or, the reaction comprises the following steps: the grafted ultrafiltration separation layer is reacted with a β-cyclodextrin aqueous solution and an amine substance aqueous solution in sequence.
6. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 5, characterized in that: The operation of reacting with the β-cyclodextrin aqueous solution satisfies one or more of the following conditions: a. The concentration of β-cyclodextrin in the aqueous solution is 1 to 10 wt%, for example, 2 wt%, 4 wt% or 8 wt%; b. The reaction temperature is 50-80°C, for example 60°C, 70°C or 80°C; c. The reaction time is 5 to 12 hours, for example 6 hours or 10 hours.
7. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 5, characterized in that: The operation of reacting with the aqueous solution of amine substances satisfies one or more of the following conditions: a. The amine substance is one or more of chitosan, polyethyleneimine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, preferably polyethyleneimine and / or chitosan; b. The concentration of the amine substance in the aqueous solution is 1 to 10 wt%, for example, 2 wt%, 5 wt% or 9 wt%; c. The reaction temperature is 60 to 90°C, for example 70°C or 90°C; d. The reaction time is 10 to 24 hours, for example 15 hours, 20 hours or 24 hours.
8. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 5, characterized in that: The method for preparing an asymmetric flat ultrafiltration membrane satisfies one or more of the following conditions: a. The ultrafiltration separation layer is a polysulfone ultrafiltration membrane; b. The vinyl carboxylic acid substance is one or more of acrylic acid, butenoic acid and pentenoic acid, preferably 2-butenoic acid or acrylic acid; c. The concentration of the solution of the vinyl carboxylic acid substance is 2wt%-20wt%, for example, 5wt%, 8wt% or 15wt%.
9. The method for preparing an asymmetric flat ultrafiltration membrane according to claim 3, characterized in that: The method also includes washing the ultrafiltration membrane after the reaction, and storing it in a 1wt% to 3wt% sodium bisulfite solution, preferably a 3wt% solution, for standby use.
10. An asymmetric flat ultrafiltration membrane obtained by the method for preparing an asymmetric flat ultrafiltration membrane according to any one of claims 3 to 9.
Citation Information
Patent Citations
Cyclodextrin modified composite organic solvent nanofiltration membrane and preparation method thereof
CN104128102A
Cyclodextrin grafted nano-material-modified organic solvent nanofiltration membrane and preparation method thereof
CN108744974A
Composite nanofiltration film and preparation method thereof
CN110917897A
Tannic acid-hydroxypropyl beta cyclodextrin composite nanofiltration membrane and preparation method thereof
CN113457468A
Membrane for removing endocrine disruptors and fabrication method thereof
KR1020110083275A